High thermoregulatory strain during competitive paratriathlon racing in the heat - Stephenson, B. T.; Hoekstra, S. P.; Tolfrey, K.; Goosey-Tolfrey, V. L. (International Journal of Sports Physiology and Performance, 2020)
Purpose: Paratriathletes may display impairments in autonomic (sudomotor and/or vasomotor function) or behavioral (drinking and/or pacing of effort) thermoregulation. As such, this study aimed to describe the thermoregulatory profile of athletes competing in the heat. Methods: Core temperature (Tc) was recorded at 30-second intervals in 28 mixed-impairment paratriathletes during competition in a hot environment (air temperature?=?33°C, relative humidity =35%-41%, and water temperature =25°C-27°C), via an ingestible temperature sensor (BodyCap e-Celsius). Furthermore, in a subset of 9 athletes, skin temperature was measured. Athletes` wetsuit use was noted while heat illness symptoms were self-reported postrace. Results: In total, 22 athletes displayed a Tc=39.5°C with 8 athletes =40.0°C. There were increases across the average Tc for swim, bike, and run sections (P=.016). There was no change in skin temperature during the race (P=.086). Visually impaired athletes displayed a significantly greater Tc during the run section than athletes in a wheelchair (P=.021). Athletes wearing a wetsuit (57% athletes) had a greater Tc when swimming (P=.032), whereas those reporting heat illness symptoms (57% athletes) displayed a greater Tc at various time points (P=.046). Conclusions: Paratriathletes face significant thermal strain during competition in the heat, as evidenced by high Tc, relative to previous research in able-bodied athletes and a high incidence of self-reported heat illness symptomatology. Differences in the Tc profile exist depending on athletes` race category and wetsuit use.